2006
DOI: 10.1111/j.1365-2907.2006.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic prey remains in the winter diet of foxes Vulpes vulpes in rural Britain

Abstract: 1. The winter diet of foxes Vulpes vulpes was quantified in seven landscape types in Britain, using faecal samples from 87 sites. 2. Medium-sized mammals (0.1-5.0 kg) were consistently the most important prey group in arable and pastural landscapes, occurring in 44-72% of scats and comprising 50-75% of the mass of prey ingested. Birds and small mammals ( < 0.1 kg) were important secondary prey groups. 3. Small mammals were the most frequently recorded prey group in marginal upland (42% of scats) and upland lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 15 publications
2
25
2
1
Order By: Relevance
“…However, it is likely that in our sites predator control was implemented irrespective of rabbit densities due to the local economic importance of pheasant and grouse shooting for which fox control represents a key management practice even at low predator density (Trout and Tittensor 1989). The fact that lagomorphs, most likely rabbits, represent the most important prey item in fox diets in the UK (Webbon et al 2006) and the observed impact of fox control on rabbit populations (Banks et al 1998) supports our finding of higher rabbit densities in areas with fox control, and suggests that this relationship is causal.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely that in our sites predator control was implemented irrespective of rabbit densities due to the local economic importance of pheasant and grouse shooting for which fox control represents a key management practice even at low predator density (Trout and Tittensor 1989). The fact that lagomorphs, most likely rabbits, represent the most important prey item in fox diets in the UK (Webbon et al 2006) and the observed impact of fox control on rabbit populations (Banks et al 1998) supports our finding of higher rabbit densities in areas with fox control, and suggests that this relationship is causal.…”
Section: Discussionmentioning
confidence: 99%
“…The red fox has a renowned generalist diet and is known to forage opportunistically (Leckie et al, 1998;Webbon et al, 2006). Although we acknowledge that we do not present clear evidence of scavenging or predation by red foxes, it is likely that the foxes were foraging within the breeding colony and could have been scavenging on seal placentae (approximately 3 kg each) or on dead or starving pups.…”
mentioning
confidence: 78%
“…It is well-documented that red fox populations suffer higher mortality rates during the winter, which occurs immediately prior to the onset of their breeding period (Heydon et al, 2000;Webbon et al, 2006). Consequently, food availability at this time of year is likely to have an important influence on pre-breeding numbers.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…During this period, the red fox prefers to prey upon species with higher biomass compensation in order to feed its cubs (Lindström, 1994;Tapper, 1995a, 1995b;Kauhala and Helle, 2000), while Lovari and Parigi (1995) found that although adult foxes preyed on bigger species, they tended to feed their cubs with smaller prey. In addition, hares are usually captured in pastures, meadows, and open agricultural land (Webbon et al, 2006;Hartová-Nentvichová et al, 2010). Wild boar was preyed upon similarly across habitats and seasons, showing only a significant temporal decrease in the red fox's diet during the third year of the study.…”
Section: Discussionmentioning
confidence: 99%